COMPOSIÇÃO DINÂMICA DE SERVIÇOS WEB SEMÂNTICOS UTILIZANDO ABORDAGENS DA ENGENHARIA DIRIGIDA POR MODELOS - BEZERRA, Eduardo Devidson Costa (2011)
The use of the Internet as a way to publish new applications and deliver new functionalities has consolidated the use of web services technology. Once web services technology enables a high degree of autonomy and interoperability, it provides a basic infrastructure for the development and composition of new services, which has benefited the business process management providing the agility required by enterprises to meet the need of rapidly changing business environment. Recently, new paradigms are being developed to deal with the increasing complexity in the development, maintenance and evolution of software systems. Among the new paradigms, Model Driven Engineering (MDE) and the Ontology stands out as the most promising for handling complex software systems. This work presents an approach to perform the dynamic composition of web services using techniques of match models (metamodels) that represent services. Models representing services must include semantic and structural aspects of the web service achieved through approaches to ontologies. Thus, we conjecture to establish matchings and measure the degree of similarity between models and investing in research about Ontologies and MDE in order to generate a tool that can assist in a Dynamic Composition of Web Services. A case study is presented to illustrate this approach.